In vitro propagation from young and mature explants of thyme (Thymus vulgaris and T. longicaulis) resulting in genetically stable shoots - Ozudogru, Elif Aylin; Kaya, Ergun; Kirdok, Emrah; Issever-Ozturk, Saliha (Springer, 2011)
An efficient in vitro propagation protocol, applicable both to young and mature explants of two Thymus spp., results in genetically stable plantlets. In vitro-grown shoot tips of Thymus vulgaris L. were exposed to cytokinins (6-benzyladenine, kinetin, and thidiazuron) alone or in combination with auxins, gibberellic acid (GA(3)) and/or silver nitrate in order to optimize in vitro shoot proliferation. Optimum shoot proliferation (97% regeneration rate, with 8.6 shoots produced per explant) was obtained when semi-solid Murashige and Skoog (MS) medium was supplemented with 1 mg L-1 kinetin and 0.3 mg L-1 GA(3). Rooting of the shoots was easily obtained on semi-solid MS medium that was either hormone-free or supplemented with auxins. However, the best root apparatus (92.5% rooting rate, with 19 adventitious roots per shoot) developed on MS medium supplemented with 0.05 mg L-1 2,4-dichlorophenoxyacetic acid. Genetic stability was confirmed in the in vitro-germinated mother plant as well as the shoots that underwent two, four, six, eight, or ten cycles of in vitro subculturing by random amplified polymorphic DNA (RAPD) analysis. When applied to the micropropagation of mature shoot tips of T. longicaulis C. Presl subsp. longicaulis var. subisophyllus (Borbas) Jalas, the optimized in vitro propagation protocol resulted in a 97.5% shoot regeneration rate, with five shoots formed per explant, and 100% rooting. Rooted plantlets of both species were transferred to 250-mL plastic pots and successfully acclimatized by gradually reducing the relative humidity.
Keywords: In vitro proliferation; Genetic stability; RAPD; T. longicaulis C. Presl subsp longicaulis var. subisophyllus (Borbas) Jalas; T. vulgaris L.